(untitled) (Anclajes, 2016)
A widely accepted hypothesis among readers and critics states that Oliverio Girondo maintained an avant-garde position throughout his literary career. However, it is possible to read an unsuccessful attempt at avoiding experimentation in his intermediate works, such as Interlunio (1937), Persuasión de los días (1942), and Campo nuestro (1946), written between two different avant-garde periods in Buenos Aires: one in the 1920s, the other in the 1950s. In analyzing these works, this paper shows Girondo’s hesitations about the idea of literary renewal following the 1920s, as well as the influence of nationalist ideals that contrast the internationalism that he had expressed in his preliminary works. It also explains his subsequent radicalization, in the late 50s, stemming from his connection with a group of young poets that sought to reclaim a place for experimentation.